حذود فعالية السياسة العقيمية لبنك الجزائر في امتصاص فائض السيولة النقدية خلال الفترة 2020/2000 : The limits of the effectiveness of the sterilization policy of the Bank of Algeria inn absorbing excess cash During the period 2000/2020 - كنيدة زليخة, (Journal of North African Economies, 2025)
This study aims to assess the effectiveness of the Bank of Algeria’s sterile policy in absorbing surplus cash durin0g the period 2000/2020. Since 2002, the Bank of Algeria has pursued a sterile monetary policy to isolate the impact of the increase in net external assets (neutralizing the effect of the surplus on the balance of payments), but it was a partially sterile policy, and beginning in 2017, with the adoption of the non-traditional financing approach, the Bank of Algeria sterilized net internal assets (neutralizing the impact of the balance-of-payments deficit) almost entirely in order to maintain the level of monetary stability monetary sterilization indicators during the study period reflected a largely acceptable efficiency by the Bank of Algeria in absorbing cash surpluses, However, they remain ineffective as required, and this study recommends the need to diversify sources of income away from the burning sector so as to avoid the risk of internal and external monetary shocks from the national economy.